Innovating Educational Publication Processes: The Role of an Automatic LoA System in JTIP - Saragih, Fadhillah Majid; Tasrif, Elfi; Darni, Resmi; Giatman, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
In this digital era, information technology has become an integral part of almost every aspect of life. In the educational context, this technology also plays an important role in facilitating the publication process of scientific articles that is more valid, practical and effective. This research aims to develop the Padang State University Journal of Information and Educational Technology (JTIP) system, especially the development of an automatic LoA (Letter of Acceptance) system. Previously, the publication management process at JTIP still used manual methods in issuing LoAs. Therefore, it is necessary to develop an automatic LoA issuance system. This research uses the Research and Development (R&D) method with a 4D model approach which includes the Define, Design, Develop and Disseminate stages. The data collection technique was carried out through a questionnaire distributed to 4 validators, 25 authors and 3 editors to test the validity, practicality and effectiveness of the system. Data analysis uses the Aiken's V validity formula to test validity, average percentage to test practicality and effectiveness. The research results show that the automatic LoA system succeeded in shortening the LoA issuance time from 5-7 days to 1 day and obtained an Aiken's V validity value of 0.87 (Valid), an average practical value of 93.5% (Very Practical), and effectiveness value with TCR of 88.8% (Very Good). It is hoped that this research can increase the practicality and effectiveness of the scientific journal publication process, especially in the context of education and technology in Indonesia. The duration of this research lasted for 6 months. Recommendations for future research are to explore the integration of this system with other publication platforms to increase the reach and accessibility of scientific publications.